A State Census of Unsubmitted Sexual Assault Kits: Comparing Forensic DNA Testing Outcomes by Geographic and Population Density Characteristics. Issue 6 (31st August 2020) - Campbell, Rebecca; Javorka, McKenzie; Sharma, Dhruv B.; Gregory, Katie; Opsommer, Matt; Schelling, Kristin; Lu, Lauren
Abstract: A growing number of U.S. cities and states have large numbers of unsubmitted sexual assault kits (SAKs) in police property facilities. Prior research conducted in large urban cities has found that testing these kits yields a sizable number of DNA profiles that meet FBI eligibility for upload to the national criminal DNA database CODIS (Combined DNA Index System) and uploaded profiles return a substantial number of matches to existing criminal profiles in CODIS. It is unknown whether these findings are unique to large urban cities with high crime rates. The purpose of current study was to document forensic testing outcomes from a state census of previously unsubmitted SAKs, which included large urban–suburban centers, as well as smaller cities and rural counties. We inventoried all previously unsubmitted SAKs in Michigan ( N = 3422 SAKs) and submitted all kits for forensic DNA testing. A total of n = 1239 SAKs had a DNA profile that met eligibility for upload into CODIS (36.2% unconditional, 56.5% conditional CODIS eligible rate) and n = 585 SAKs yielded a CODIS Hit (17.1% unconditional, 47.2% conditional CODIS hit rate). These rates are consistent with studies from urban areas suggesting approximately half of SAKs tested yield a CODIS profile and approximately half of those uploaded profiles yield a hit. We compared SAK forensic testing outcomes by geographic and population density characteristics, and although rates were often higher in larger metropolitan areas, the obtained rates in micropolitan and rural areas suggest testing is warranted in smaller jurisdictions as well.